Curious George visits the library - 20160731 frey50; Rey, Margret; Rey, H. A. 1898-; Weston, Martha (Boston : Houghton Mifflin, 2003)
George is lucky to arrive at the library just in time for story hour. But it's not easy for a little monkey to sit still too long. From selecting books to getting his very own library card, George's day at the library makes reading fun.
Keywords: Librarys; Curious George (Fictitious character); Monkeys; Librarys; Curious George (Fictitious character); Monkeys